A SYSTEMIC FUNCTIONAL INTERPRETATION OF CURRENT INDONESIAN VERBAL GROUP STRUCTURES - Budiasa, I Gede (Lingual: Journal of Language and Culture, 2014)
The current study attempts to describe and analyze the contemporary Indonesian Verbal Group seen from the two metafunctions. It includes Transitivity Structures or ideational meaning and Mood Structures or interpersonal meaning of contemporary Indonesian Verbal Group in Short Story. The corpus data comprising 160 verbal groups and 130 processes is analyzed on descriptive and qualitative bases. The findings reveal that the experiential and logical function of Mood Structures of Current Indonesian Vebal Groups are mostly formulated as Predicator or event only (78%). Few is formulated as Verbal Group Complexes included Hypotactic Verbal Groups of Phase or elaborating a process (1.3%), of Modulation or enhancing a process (1.9%) and of Conation or extending a process (0.6%). As far as the simple verbal group structure is concerned, Modulated Operator ^ Predicator occupies the second position (5%) in terms of its occurrence. The third position is occupied by Polarity Operator or Negator ^ Predicator (3.8%) and followed by respectively Adjunct ^ Predicator (1.9%), Negator ^ Adjunct ^ Adjunct ^Predicator (1.8%), Negator ^ Modality Operator ^ Predicator (1.3%) With regard to the transitivity structure of Indonesian Verbal Groups, experientially the corpus data in the text under study is dominated by material process as a process of doing and happening